LAND COVERAGE CHANGES AND FRAGMENTATION OF MANGROVES IN THE SOCONUSCO REGION, CHIAPAS, MEXICO, 1994-2011 - Romero-Berny, Emilio I.; Acosta-Velázquez, Joanna; Tovilla-Hernández, Cristian; Schmook, Birgit; Gómez-Ortega, Rocio (Revista Geográfica de América Central., 2016)
We analyzed the spatial dynamics of the mangrove coverage of El Cabildo-Amatal-Gancho Murillo coastal wetland in Chiapas, Mexico by determining their impact by fragmentation processes. The analysis of changes showed a loss of 509 ha of mangrove in a 17-year period and an annual deforestation rate of 1.05 %. The metrics indicate that the system was composed of 38 largest mangrove patches greater than 0.36 ha in 2011, which represents an increase of 58% regarding its size in the year 1994. The fractal dimension of 1.4 and the fragmentation rate estimated suggest that the landscape has been impacted. Altogether, the results show that, due to changes in the system, it is necessary to implement coastal management plans.